Komunikasi Interpersonal Pada Komunitas Dakwah Binaan Nusukan Dari MTA Dalam Membentuk Ukhuwah - Fatkhul Putra Perdana; Rina Sari Kusuma (Komunika, 2019)
This research is motivated by Indonesia as a predominantly Muslim country, giving rise to a variety of da'wah organizations such as the Majlis Tafsir Al- Qur'an (MTA). The presence of this community organization gave rise to the model of brotherhood formation through the stages of interpersonal communication. This research is a descriptive qualitative research and uses the population of all members of the Nusukan fostered community from MTA. The sampling used is the snowball sampling model. Data collection uses in-depth interviews, documentation and observation. Data validity uses triangulation of data sources. The results of this study are the stages of forming ukhuwah. First, Ta'aruf, which occurs as the initial stage of effective interpersonal communication, involves the stages of contact and orientation. Second, Tafahum as a means of understanding deeper between members through interpersonal communication involves the stages of involvement. Third, ta'awun as interpersonal communication in fostering mutual care which includes the stages of involvement but tends towards the stages of familiarity. Fourth, takaful in interpersonal communication so as to form a sense of brotherhood covering the stages of intimacy and improvement.